Fifty plus in Ireland 2011: First results from The Irish Longitudinal Study on Ageing (TILDA) - NORMAND, CHARLES; BARRETT, ALAN; O'SULLIVAN, VINCENT; WHELAN, BRENDAN JAMES; O'REGAN, CLAIRE; MATY, SIOBHAN; KAMIYA, YUMIKO; SAVVA, GEORGE; LAYTE, RICHARD; MOSCA, IRENE; KENNY, ROSE ANNE; TIMONEN, VIRPI (Trinity College Dublin, 2011)
The Irish Longitudinal Study on Ageing (TILDA) is a large-scale, nationally representative study of people aged 50 and over in Ireland. It is the most ambitious study of ageing ever carried out in Ireland and represents a step-change in terms of data, knowledge and understanding of ageing with which to inform policy and novel research. TILDA is designed to maximise comparability with other well-established international longitudinal studies. More than 8,000 people aged 50 and over accepted the invitation to participate in the first wave of TILDA, and the majority of these also agreed to undertake a comprehensive health assessment. Contents Executive Summary 1. Introduction - Rose Anne Kenny and Alan Barrett 2. Socio-Demographic Characteristics Of Older People In Ireland - Yumiko Kamiya and Nick Sofroniou 3. Older People As Members Of Their Families And Communities - Yumiko Kamiya and Virpi Timonen 4. Social Engagement Of Older People - Virpi Timonen, Yumiko Kamiya and Siobhan Maty 5. Physical And Behavioural Health Of Older Irish Adults - Hilary Cronin, Claire O?Regan and Rose Anne Kenny 6. Mental Health And Cognitive Function - Claire O?Regan, Hilary Cronin and Rose Anne Kenny 7. Health And Social Care Utilisation - Charles Normand, Yumiko Kamiya, Virpi Timonen and Brendan Whelan 8. Retirement And Labour Market Participation - Irene Mosca and Alan Barrett 9. Income and Asset Levels of Older People - Vincent O? Sullivan and Richard Layte 10. Quality Of Life And Beliefs About Ageing - Hannah McGee, Karen Morgan, Anne Hickey, Helen Burke and George Savva 11. Methodology - George Savva
PUBLISHED
Dublin
Keywords: Gerontology; Irish Longitudinal Study on Ageing (TILDA)